Nearpod-assisted PBL enactment within the TPACK framework: Transforming mathematics learning to enhance problem solving skills and digital literacy - Hafsah Adha Diana; Nadya Syifa Utami; Fatimah Fatmawati (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2026)
Technology integration in mathematics learning requires a theoretically grounded design rather than simple digital adoption. Within the Technological Pedagogical and Content Knowledge (TPACK) framework, Problem-Based Learning (PBL) represents pedagogical knowledge, and Nearpod represents technological knowledge. This study does not propose a new model; instead, it operationalizes TPACK through a structured instructional enactment that aligns statistical content, PBL inquiry phases, and Nearpod affordances. A quasi-experimental pretest–posttest control group design was employed with twelfth-grade students. Baseline equivalence between the experimental and control groups was confirmed using an independent-samples t-test. Enhancement in mathematical problem-solving was analyzed using gain scores, independent-samples t-tests, and two-way ANOVA. Results revealed a significant difference in scores gained between groups. A significant main effect of the instructional approach and an interaction effect with initial ability were found. Digital literacy also differed significantly between groups. These findings demonstrate that TPACK becomes instructionally meaningful when statistical content is transformed through structured inquiry and technology-mediated representation, although students’ initial mathematics ability moderates’ effectiveness.